Beeswax foundations with impregnated thymol for Varroa control - Garção, Hélder (2005)
The use of essential oils and organic acids is generally accepted as an alternative tool for the control of the Varroa Destructor levels in bee's colonies, avoiding mite resistance and reducing the residues contaminations resulting from the systematic application of synthetic chemicals.